Integrated pressure relief technology for rock burst and gas outburst coordinated control in ultra-thick coal seams under spatially isolated rock pillar areas - Xianggang WANG; Hu HE; Shifan ZHANG; Shenghua XUE; Yongkang HE; Xin NIU; Yu LUO (Meikuang Anquan)
With the increasing depth of coal mining and the complexity of mining technical conditions, some mines are facing dual dynamic disasters of rock burst and coal and gas outburst, which exhibits a mutually coupled inducing trend. This study took a typical rock burst and gas outburst coal mine as the engineering background, studied the stress distribution law of extremely thick coal seam under the influence of the space “isolated rock pillar” formed by oil shale mining, and proposed the regional integrated pressure relief technology along the seam with ultra-deep and large diameter drilling and through the ultra-high pressure hydraulic slotting zone. The results indicate that: the vertical stress of the roadway in the coal seam under oil shale goaf is relatively low (all below 4 MPa), demonstrating significant pressure relief effects from protective seams; in spatial rock pillar influencing areas, the vertical peak stress of the roadway approaches 20 MPa, five times higher than that under protective seams and the stress concentration range is relatively larger than normal, which exhibits a state of regional high stress. Compared with traditional “pressure relief along with excavation” modes, integrated pre-pressure relief can reduce peak abutment pressure around roadways, eliminate pressure relief blind zones, significantly decrease the compaction possibility and enhance pressure relief timeliness. In 200 mm borehole diameter and 0.5 m spacing in integrated pressure relief conditions, roadway deformation becomes smaller than that in traditional scenarios; both micro seismic frequency and energy remain stable during roadway excavation and coal mining in rock pillar affected areas, with measured residual gas content decreasing to 4.73 m3/t, demonstrating remarkable combined rock burst and gas outburst prevention effects.